(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Corticosteroid is popular medication used to treat various conditions like autoimmune diseases, skin disorders etc. But prolong use can cause numerous side effects including steroid withdrawal syndrome, insomnia, gastrointestinal symptoms, weight gain, osteoporosis. Here is a case of skin disorder developed after two years of continuous use of oral corticosteroids which was managed in IPD level using Ayurvedic principles and found to be effective. The condition was considered as Visarpa with Dusivisha involvement. Treatment was planned according to the signs and symptoms of the patient. Sodhana was done followed by Shamana chikitsa. Unique Yogas mentioned in Keraleeya visha chikitsa textbooks like Nalpamaraadi yoga, Visavilwadi yoga etc. were used for treatment. After IP treatment follow up was done for 1 month. The skin lesions got complete relief remaining some hyperpigmented scars.